Аналіз особливостей сучасних застосунків для пошуку рецептів за продуктами харчування - Боцвін, О. С. (ХНУРЕ, 2025)
This work analyzes the features of modern applications that help users find recipes based on the ingredients they have at home. As more people look to make meals without shopping for extra items, these apps have become important tools. The study looks at apps like Cookpad, retsepty.online.ua, My Fridge Food, and Supercook, comparing how they work and what users like or dislike about them. While these apps make it easier to cook with what’s on hand, they have some issues, like including extra ingredients users didn’t choose and being tricky to navigate. This analysis highlights the advantages and disadvantages of current applications, which can be improved when creating new apps.
Keywords: продукти харчування; рецепт